Emission inventory of criteria pollutants Costa Rica in 2011 - Herrera, Jorge (2014)
Criteria pollutant emissions were determined in Costa Rica in 2011, from the application of emission factors, measurement sources, the application of mechanistic models and material balance. A total of 1,898,591 tons of criteria pollutants which were recorded, mobile sources are the main contributions with nearly 61%, followed by the area and stationary sources, with 21 and 18 % respectively. The most abundant pollutant in weight, anthropogenically generated during 2011 was the carbon monoxide ( CO ), issuing into the atmosphere about 856 264 tonnes per year, mainly for mobile sources; next in order of importance emissions of total organic gases (GOT) with more than 434 777 tonnes per year, with mobile sources which generate 40%.